Research on University Teachers’ Intention to Adopt Interactive Mobile Teaching Tools and the Barriers Based on the TAM Model - Yue, Gabriel Xiao-Guang; Imanova, Mehriban; Hadjiphanis, Lycourgos; Mao, PingTing; Chen, Xiangliu (International Journal of Interactive Mobile Technologies (iJIM), 2026)
With the deep integration of mobile technology and higher education, interactive mobile teaching tools have gradually occupied an important position in teaching activities in colleges and universities. However, university teachers, as core users of new teaching technologies, still face many obstacles in their willingness to use mobile teaching tools. Based on the technology acceptance model (TAM), combined with the results of data collection through questionnaires, this study uses structural equation modeling (SEM) to explore university teachers’ intention to apply (IU), interactive mobile teaching tools and the barrier factors they encounter. The study findings show that perceived ease of use (PEOU) affects perceived usefulness; PEOU affects attitude towards use; perceived usefulness (PU), affects IU; technical barriers (TB) and management barriers (MB) affect PU, TB affect PEOU, and IU depends on previous mobile teaching experience (TE). The conclusions of this study suggest that colleges and universities should improve the adoption rate and the depth of teaching integration of interactive teaching tools among university teachers by optimizing the school management and support system, promoting the adaptation of tool design to teaching needs, building an experience transfer and community support network, and carrying out phased pilots and effect iterations.